1995
DOI: 10.1088/0953-8984/7/7/013
|View full text |Cite
|
Sign up to set email alerts
|

Photoconduction in a polydiacetylene film

Abstract: Steady state photoconductivity, optical absorption and dark conductivity measurements in thin films of polydiacetylene ((8-butoxycarbonyl)methylurethanyl)-1-(5-pyrimidyl)octa-1, 3-diyne (PDA-BPOD) are reported. Steady state photoconductivity results are discussed within the framework of the one-dimensional Onsager theory of geminate recombination. The photoconductivity action spectrum shows a peak at 1.9 eV and a direct band to band transition above 2.4 eV. The absorption spectrum at 50 K is red shifted with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Amphiphilic long-chain diacetylene monomers, compressed at the air−water interface and then UV polymerized, form an ultrathin, stable trilayer structured Langmuir film (LF). A PDA LF formed on water has unique strand morphology parallel to the polymer direction as a result of its rigid and unbranched linear structure, which provides it with mechanical and chemical stability. This, along with the unique electro-optical properties of PDAs, make them attractive materials for a variety of technological applications such as chemical and biological sensors, resist for lithography, , effective template for oriented nucleation of inorganic crystals such as calcite , and semiconducting nanocrystals. …”
Section: Introductionmentioning
confidence: 99%
“…Amphiphilic long-chain diacetylene monomers, compressed at the air−water interface and then UV polymerized, form an ultrathin, stable trilayer structured Langmuir film (LF). A PDA LF formed on water has unique strand morphology parallel to the polymer direction as a result of its rigid and unbranched linear structure, which provides it with mechanical and chemical stability. This, along with the unique electro-optical properties of PDAs, make them attractive materials for a variety of technological applications such as chemical and biological sensors, resist for lithography, , effective template for oriented nucleation of inorganic crystals such as calcite , and semiconducting nanocrystals. …”
Section: Introductionmentioning
confidence: 99%
“…All compounds (R 3 N)In are metallic, with the magnetic properties dominated by the rare-earth metal ions. [55] While La 3 In shows a superconducting transition at T c ≈ 10 K, [56] (La 3 N)In lacks any indication for superconductivity. Earlier it was observed that T c does not significantly change with introduction of O or B into La 3 In within the full range of 0 ≤ x ≤ 1 in cubic (La 3 Z x )In, while T c decreases continuously upon addition of carbon.…”
Section: Inverse Perovskite Nitrides With Indium: (R 3 N)inmentioning
confidence: 99%
“…Polydiacetylene (PDA) and its derivatives are attractive materials for electronics and photonics 1) since the PDA films of fine quality are formed by use of Langmuir-Blodgett, 2,3) vacuum evaporation 4) and the spin-coating 5) techniques. It has photo conductivity 6,7) and nonlinear optical (NLO) properties, arising from its -conjugation system. Many studies have been appeared on nonlinear optics, [8][9][10][11][12][13][14][15] electrical absorption, [16][17][18] unique optical elements [19][20][21][22] and sensing applications.…”
Section: Introductionmentioning
confidence: 99%